The Relationship between Organizational Cynicism and Organizational Anti-Citizenship Behavior with the Mediating Role of Organizational Envy - آسیه رئیسی; ناصر ناستی زایی (مشاوره شغلی و سازمانی, 2019)
The purpose of this study was to determine the relationship between organizational cynicism and organizational anti-citizenship behavior with the Mediating Role of organizational envy. The following survey was done with descriptive and structural equation modeling type. By Stratified randomized sampling 191 teachers of Zahedan were studied with through three questionnaires including organizational cynicism, organizational anti-citizenship behavior and organizational envy. For data analysis the correlation coefficient and simultaneous multiple regression were used by SPSS21 and Lisrel. Based on results there was a positive and significant relationship between organizational cynicism, organizational anti-citizenship behavior and organizational envy. Organizational cynicism did not directly affect organizational anti-citizenship behavior but indirectly, through the organizational envy variable, had a positive effect on organizational anti-citizenship behavior. Thus the result of the expansion of organizational cynicism is organizational envy; the consequence of organizational envy is the appearance of organizational anti-citizenship behaviors. Since the root of organizational cynicism goes back to distrust, managers can reduce the organizational cynicism of employees by extending organizational trust.